Immunogenicity and safety of an inactivated enterovirus 71 vaccine co-administered with measles-mumps-rubella vaccine and live-attenuated Japanese encephalitis vaccine: a phase 4, single-center, randomized controlled trial - Xiaoyu Liu; Wanqi Yang; Chao Zhang; Heng Wu; Ruize Wang; Qiang Ding; Yan Hu; Yongli Xiong; Shaobai Zhang; Lin Wang (Taylor & Francis Group, 2021)
Co-administration of vaccines could be an efficient strategy to increase vaccination uptake and reduce the number of clinic visits. This randomized controlled study aimed to evaluate the immunogenicity and safety of enterovirus 71 (EV71) vaccine co-administered with measles-mumps-rubella (MMR) vaccine and live-attenuated Japanese encephalitis vaccine (LA-JEV). A total of 372 healthy infants were randomly assigned in a 1:1:1 ratio to receive simultaneous administration of EV71 vaccine (dose 1) and MMR on d 0 and EV71 vaccine (dose 2) and LA-JEV on d 30 (Group 1); administration of MMR and LA-JEV on d 0 and 30, respectively (Group 2); or administration of doses 1 and 2 of EV71 vaccine on d 0 and 30, respectively (Group 3). The non-inferiority analysis of the seroconversion for EV71 neutralizing antibody after vaccination was the primary outcome. According to per protocol set, antibody response against EV71, measles, mumps, rubella, and Japanese encephalitis (JE) virus was similar regardless of administration schedule. After vaccination, the seroconversion rate of EV71 neutralizing antibody in Group 1 (107 [97.27%] of 110) was non-inferior to that in Group 3 (109 [97.32%] of 112; difference - 0.05% [95% CI - 5.38 to 5.21]). The incidences of adverse reactions were 62.60% (77/123) in Group 1, 54.84% (68/124) in Group 2, and 37.70% (46/122) in Group 3, and most of them were mild to moderate in severity. No vaccine-related serious adverse events were reported. In total, the co-administration of combined EV71 vaccine with MMR and LA-JEV showed no interference with antibody response and demonstrated good safety profiles.